Rapprochement Urbanism: An Exploration into the Rewilding of Jackson, Mississippi - Pierce, West Kendon; Gregory, Alexis (Enquiry The ARCC Journal for Architectural Research, 2019)
Rapprochement urbanism addresses how wild environments can be accommodated in urban spaces to create more sustainable and resilient cities. Referring to the dual realities of wilderness and urbanity, this design strategy explores the interaction of their two structures to replace the misconception that cities are built "on” the natural environment, with the assertion that cities are built "in” it. Jackson, Mississippi currently treats adjacent vibrant ecological habitats as forgotten back alleys rather than urban assets. Utilizing interventions within a holistic plan, rapprochement urbanism combats urban sprawl and "back alley” attitudes, mitigates stormwater challenges, and facilitates human and animal spatial needs. Rapprochement urbanism, through the rewilding of Jackson, MS, allows architects to more directly impact and improve the ecological sustainability of this city of 170,000 inhabitants.[i] i"Jackson, Mississippi.” Jackson, Mississippi (MS) Profile: Population, Maps, Real Estate, Averages, Homes, Statistics, Relocation, Travel, Jobs,Hospitals, Schools, Crime, Moving, Houses, News, Sex Offenders. http://www.city-data.com/city/Jackson -Mississippi.html (Accessed November 01, 2018).